Comparative Analysis of Potential Halal Product Exports of Indonesia in ASEAN + 3 Countries - Indanazulfa Qurrota A'yun (UNIVERSITAS MUHAMMADIYAH METRO, 2021)
This study aims to examine the comparison of potential halal product exports in several ASEAN countries and several Islamic countries outside ASEAN. Commodities used in this study consisted of meat, coffee, dairy products, sugar, cereals and fruits. To support the purpose of this study, the data used were sourced from the UN Comtrade with a research period from 2009 to 2019. The countries sampled in this study consisted of Indonesia, Thailand, Singapore, the Philippines, Brunei Darussalam, Malaysia, Turkey, Saudi Arabia, and India. This study found that Indonesia has an advantage in terms of coffee commodity. This can be seen from the RCA value of 4.29. Meanwhile, for the commodities of fruits and nuts, Indonesia had the smallest specialization index value, namely 0.95. Indonesia's strongest competitors in ASEAN are Malaysia and Thailand for commodity sugar products and dairy products. However, when analyzed by including India, Turkey and Saudi Arabia, it shows that India is the strongest competitor and controls market share. Furthermore, when compared to ASEAN countries, Indonesia's commodity exports still dominate the market share compared to the Philippines and Brunei Darussalam. It can be concluded that Indonesia's export products still have the ability to compete and have a high market share in ASEAN +3. If Indonesia intensively provides the halal label, this will not only increase exports but also to meet the needs of Indonesian citizens who are predominantly Muslim.